142k views
2 votes
Write the smaller solution first, and the larger solution second.

f (x)=(x -3)(2x -8)
smaller x=
larger x=

User Jlmmns
by
5.7k points

2 Answers

5 votes

Answer:

x = 3, x = 4

Explanation:

Given

f(x) = (x - 3)(2x - 8)

To find the solutions let f(x) = 0, that is

(x - 3)(2x - 8) = 0

Equate each factor to zero and solve for x

x - 3 = 0 ⇒ x = 3

2x - 8 = 0 ⇒ 2x = 8 ⇒ x = 4

Thus

smaller solution x = 3

larger solution x = 4

User BastiBen
by
6.1k points
1 vote

Answer:

x = 3,x=4

Explanation:

easy, make each parentheses equal to 0.

so (x-3) = 0

(2x-8) = 0

then now solve for x in each case

User ANUP SAJJAN
by
6.2k points